LISINOPRIL AND BLOOD PRESSURE REGULATION IN HYPERTENSIVE PATIENTS WITH DIABETES MELLITUS. (June 2018) - Radivojevic, N.; Stojanov, V.; Paunovic, K.; Jakovljevic, B.; Marjanovic, M.
Abstract : Objective: The aim of this study was to assess the regulation of blood pressure (BP) after three months of antihypertensive therapy in patient with type 2 diabetes mellitus. Design and method: The study sample consisted of 398 patients with arterial hypertension and type 2 diabetes (144 men and 254 women), aged 63.9 ± 9.6 years. Hypertension was treated with 10 mg lisinopril (98 patients), 20 mg lisinopril (140 patients), and fixed combination of 20 mg lisinopril and 12.5 mg hydrochlorothiazide (160 patients). BP was measured by an oscillometric device at the beginning of the study, one month later and after three months of therapy. A well-regulated blood pressure was defined if systolic pressure (SBP)/diastolic pressure (DBP) were less than 140/90 mmHg one month and three months after the initiation of therapy. Logistic regression was used to predict good regulation of SBP and DBP after three months of therapy in relation to age, gender, smoking habits, body mass index (BMI), and regulation of blood pressure one month after the beginning of therapy. Results: At the beginning of the study, the average SBP in patients with diabetes was 159.4 ± 12.7 mmHg, DBP 96.3 ± 8.5 mmHg. After one month, average SBP was 140.5 ± 18.6 mmHg, DBP 87.8 ± 8.1 mmHg. At that stage, SPB was well-regulated in 127 patients (31.9%), whereas DBP was well-regulated in 189 patients (47.5%). After three months of therapy, average SBP was 132.4 ± 9.0 mmHg, DBP 81.6 ± 6.0 mmHg. At that stage, SPB was well-regulated in 286 patients (71.9%), whereas DBP was well-regulated in 339 persons (85.2%). The only significant predictor for the good regulation of BP after three months of therapy was good regulation of SBP one month after the beginning of therapy (Odds Ratio = 2.44; 95% Confidence Interval = 1.44–4.13) and good regulation of DBP one month after the beginning of therapy (Odds Ratio = 8.08; 95% Confidence Interval = 3.71–17.63). These prediction models were independent from age, gender, BMI and smoking habits. Conclusions: The regulation of systolic and diastolic pressure after three months of antihypertensive therapy with lisinopril depends significantly on the achievement of good regulation of blood pressure one month after the initiation of therapy.